PERNIKAHAN CINA BUTA DAN GENDER - Faisal Faisal (Jurnal Anifa: Studi Gender dan Anak, 2023)
Cina Buta in Arabic is muhallil. Muhallil is the one who causes because of his work to be lawful or that marriage is permissible. Cina Buta marriage is not as easy as turning the palm of the hand for couples who have divorced to separate and give up their respective partners, especially since there is still love and desire to return which is added to the child and economic factors. Cina Buta marriage is a concrete solution for married couples who have divorced thalak tiga but want to return again to sail the ark of the household again. The study of Cina Buta marriage is according to the gender view, which is important by looking at the benefits and benefits of both the husband or ex-wife or muhallil.